A Study of the Growth of Human Foetal Lung in Relation with the Gestational Age - Rajeev Mukhia (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Lung is one of the organs of interest for researchers since a long time. Though detailed study about adult lung is there in the literature but study of lungs at different stages in the fetal period is far and few. Aim: The present study attempted to find out the relationship between the foetal lungs in relation with its development in different gestational weeks. Materials and Methods: The study was carried out on 40 spontaneously aborted human foetuses of known gestational age ranging from 10 weeks to 40 weeks. The anterior thoracic wall was dissected and the lungs were removed from the thoracic cage. The weight of the foetuses and foetal lung was measured in grams on digital weighing machine. The mean values of all parameters by gestational age were calculated. Data of the study were statistically analysed by using the Microsoft Excel 2007 program. Results: The average weight of right lung at 10th to 15th week and 36th to 40th week was 2.0 and 25.7 gm respectively. The average weight of left lung at 10th to 15th week and 36th to 40th week was 1.8 and 25.2 gm respectively. The body weight of foetuses showed gradual increase from 30 to 2712 gm at 10th week to 40th week of gestation. Conclusion: Evaluating body and lung weights and measurements against known standards is an important part of perinatal pathology. It also provides new insights to the anatomist and clinician for understanding and developing knowledge in both normal and pathological conditions of pulmonary tissue.